Sifat kimia, dan fungsional mocaf (modified cassava flour) dengan perbedaan suhu dan waktu pregelatinisasi - Saskia Fitriana; Nurud Diniyah; Achmad Subagio; Eko Priyantono; Eka Rahayu; Mahrus Irsyam (AGROINTEK, 2026)
Starch can be modified through physical treatment, particularly by using the pregelatinizing technique. Pregelatinizing is a hydrothermal modification process that involves heating starch beyond its gelatinization temperature. This treatment improves the physicochemical and functional characteristics of starch (MOCAF), thereby enhancing its performance in various applications. This study aims to determine the effect of temperature and pre-gelatinization time on the physicochemical and functional properties of pregelatinizing of MOCAF. The research method used a randomized block design (RBD) with two factors. The factor A was heating time (10, 15, and 20 minutes), and factor B was heating temperature (90, 100, and 1100C). The parameters of the observations made include syneresis, swelling power, solubility, Water Holding Capacity (WHC), Oil Holding Capacity (OHC), moisture content, ash content, starch content, amylose content, and amylopectin content with two repetitions. The best results showed the treatment of 20 minutes heating time and a temperature of 1100C with characteristics syneresis 0.45 ± 0.02 (g/g); swelling power 19.64 ± 0.41 (%); solubility 10.30 ± 0 .40 (%); WHC 235.52 ± 0.43 (%); OHC 159.13 ± 0.37 (%); moisture content 9.92 ± 0.08 ( %); amylopectin content 57.75±0.21 (%); amylose content 31.22±0.01 (%); and starch content 85.20±0.02 (%). Modification methods using pregelatinizing MOCAF with temperature treatment and heating time had a significant effect on syneresis, swelling power, solubility, WHC, OHC, moisture content, ash content, amylose content, starch content, and amylopectin content so, MOCAF with pregelatinizing can be widely used for applications in the food, cosmetic, pharmaceutical and paper industries.